Super Edge Antimagic Total Labeling On Disjoint Union Of Cycle With Chord - Listiana, Yuni (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2017)
A graph with order and size is called -edge antimagic total ( -EAT) if there exist integers , and a bijection such that , where . An -EAT labeling of graph is super if . In this paper we describe how to construct a super -EAT labeling on some classes of disjoint union from non isomorphic graphs, namely disjoint union of cycle with cycle with chord . Keywords: -edge-antimagictotallabeling,super -edgeantimagictotalla- belling, cycle with chord,